جهود العلماء في نشر الوسطية والاعتدال قديما وحديثا وجهود علماء جنوب شرق آسيا خاصة - Omar Kalash (Islam Futura, 2020)
The religious moderation adhered to by Muslims is based on following the religion of Islam, which calls for righteousness, mercy and justice in words, deeds and beliefs. The method of Talaqqi in which Muslim scholars whether Salaf or Khalaf used a long time ago has contributed in spreading moderation. This method was one of the most important things Muslim scholars used to combat the spread of extremist ideas and to preserve Islamic heritage science for the following generations. This method is also used by south east Asia scholars, but in this era it is facing many challenges because of extremists who wants to destroy this method in order to open the way for themselves to spread new extremist ideas and false doctrines that are contrary to the believes of true Salaf and Khalaf. Therefore we have to adhere to the method of Talaqqi to maintain moderation.